2003
DOI: 10.1177/0001699303046004002
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Demographic Effects on Cultural Biases: A Nordic Study of Grid-Group Theory

Abstract: Grid-group theory claims that patterns of social relations only, and not socio-demographic characteristics, can account for biases, of which the theory prescribes four: hierarchy, egalitarianism, individualism and fatalism. Survey analysts conventionally employ respondents' socio-demographic correlates when accounting for values. We take the value survey strategy and apply it to grid-group theory's four biases. Employing a 1999 survey administered in Iceland, Norway, Denmark, Sweden and Finland (n = 4,832), we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…The questionnaire operationalizes items that encompass the grid/group construct, which have been shown to be associated with sociodemographic characteristics (77). Pilot testing was conducted with these items with an ethnically diverse convenience sample.…”
Section: Sidebarmentioning
confidence: 99%
“…The questionnaire operationalizes items that encompass the grid/group construct, which have been shown to be associated with sociodemographic characteristics (77). Pilot testing was conducted with these items with an ethnically diverse convenience sample.…”
Section: Sidebarmentioning
confidence: 99%
“…With regard to egoistic values, because it has been shown that men are more individualistic than women ( Grendstad and Sundback, 2003 ), it is assumed that men will more strongly endorse egoistic values than women will. The sparse empirical evidence related to this hypothesis, however, seems to show no difference in egoistic values by gender (i.e., Ndofirepi, 2019 ; d = 0.11).…”
Section: Introductionmentioning
confidence: 99%
“…Moving on to the age hypothesis, younger people are thought to be more concerned about environmental issues than older people, partly because environmental issues have been prominent throughout young people’s lives ( Grendstad and Wollebaek, 1998 ), and partly because the former are less integrated into the existing social order ( Van Liere and Dunlap, 1980 ; Grendstad and Sundback, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…To operationalize the grid/group construct we used items developed originally for use in the Nordic countries which are independent of any specific political proposals and have previously been associated with socio-demographic characteristics. (34) We also included items from the Multi-Dimensional Health Locus of Control Scale (MHLC),(35) and the Perceived Stress Scale. (36) Because of limited space on the questionnaire, we used a truncated version of the grid-group scale, excluding a “fatalism” sub-scale and using selected items from what were originally separate “hierarchy” and “egalitarianism” sub-scales.…”
Section: Methodsmentioning
confidence: 99%